2017
DOI: 10.1371/journal.pone.0172681
|View full text |Cite
|
Sign up to set email alerts
|

The single nucleotide variant rs12722489 determines differential estrogen receptor binding and enhancer properties of an IL2RA intronic region

Abstract: We studied functional effect of rs12722489 single nucleotide polymorphism located in the first intron of human IL2RA gene on transcriptional regulation. This polymorphism is associated with multiple autoimmune conditions (rheumatoid arthritis, multiple sclerosis, Crohn's disease, and ulcerative colitis). Analysis in silico suggested significant difference in the affinity of estrogen receptor (ER) binding site between alternative allelic variants, with stronger predicted affinity for the risk (G) allele. Electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…In the case of TFBS prediction for the analysis of regulatory networks, the D-quality models may notably reduce performance ( 41 ). However, other applications such as annotation of regulatory sequence variants ( 42 , 43 ) may benefit from additional TFs and alternative binding models. Thus, starting from this release we provide two collections: the CORE collection of the most precise models (ABC quality) recommended for TFBS predictions for annotation of regulatory regions, and the FULL collection that includes alternative models and models of lower quality (D), which can be used for exploratory purposes.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of TFBS prediction for the analysis of regulatory networks, the D-quality models may notably reduce performance ( 41 ). However, other applications such as annotation of regulatory sequence variants ( 42 , 43 ) may benefit from additional TFs and alternative binding models. Thus, starting from this release we provide two collections: the CORE collection of the most precise models (ABC quality) recommended for TFBS predictions for annotation of regulatory regions, and the FULL collection that includes alternative models and models of lower quality (D), which can be used for exploratory purposes.…”
Section: Discussionmentioning
confidence: 99%
“…There are a few examples where, among the many signals resulting from GWAS, the causal variant and the underlying mechanism has been defined, such as the following. SNPs in the interleukin 2 receptor gene seem to differently influence various autoimmune diseases [17][18][19]. Likewise, variants of TYK 2 locus resulting from GWAS in different immune-mediated conditions normally mediate a balanced genetic effect, warranting a trade-off between autoimmunity and immunodeficiency [20].…”
Section: Introductionmentioning
confidence: 99%
“…This finding suggested that patients carrying the "TT" genotype at rs9679162, actually harbor a 5 kb genomic region (around GALNT14-rs9679162), which is genetically different from those from the "non-TT" genotype. The sequence differences may thereby impact GALNT14 mRNA and protein expression, as variations in the intron region have been found to affect many aspects of regulatory events for gene expression, including transcription efficiencies and alternative splicing [17][18][19][20][21]. This view is supported by the findings that the expression levels of GALNT14 are different between patients with the "TT" and "non-TT" genotypes.…”
Section: Discussionmentioning
confidence: 94%